Intensifying Continuous Production of Gag-HA VLPs at High Cell Density Using Stable Insect Cells Adapted to Low Culture Temperature - Fernandes, Bárbara; Correia, Ricardo; Alves, Paula M.; Roldão, António (Frontiers in Bioengineering and Biotechnology, 2022)
Protein production processes based on stable insect cell lines require intensification to be competitive with the insect cell-baculovirus expression vector system (IC-BEVS). High cell density (HCD) cultures operated in continuous mode, capable of maintaining specific production rates for extended periods of time may lead to significant improvements in production yields. However, setting up such processes is challenging (e.g. selection of cell retention device, optimization of dilution rate), often demanding the manipulation of large volumes of culture medium with high cost associated. In this study, we developed a process for continuous production of Gag virus-like particles (VLP) pseudotyped with a model membrane protein (influenza hemagglutinin, HA) at HCD using stable insect cells adapted to low culture temperature. The impact of cell retention device (ATF vs TFF) and cell specific perfusion rate (CSPR) on cell growth and protein expression kinetics was evaluated. Continuous production of Gag-HA VLPs was possible using both retention devices and CSPR of 0.04 nL/cell.d, TFF inducing higher cell lysis when compared to ATF at later stages of the process (kD = 0.009 vs 0.005 h-1, for TFF and ATF respectively). Reducing CSPR to 0.01-0.02 nL/cell.d using ATF had negligible impact on specific production rates (rHA = 72-68 titer/109 cell.h and rp24 = 12-11 pg/106cell.h in all CSPR) and on particles morphology (roundshape structures displaying HA spikes on their surface) and size distribution profile (peaks at approximately 100 nm). Noteworthy, at these CSPRs, the amount p24 or HA formed per volume of culture medium consumed per process time increases by up to 3-fold when compared to batch and perfusion operation modes. Overall, this work demonstrates the potential of manipulating CSPR to intensify the continuous production of Gag-HA VLPs at HCD using stable insect cells for making them an attractive alternative platform to IC-BEVS.